Testing SCAPM and CAPM On Sharia Stock Portfolios: Evidence From The Jakarta Islamic Index (JII) For The 2019–2023 Period - Abdullah Samy Assyakiri; Muslimin Muslimin; Ahmad Faisol (International Journal of Economics, Commerce, and Management, 2025)
This study examines and compares the Capital Asset Pricing Model (CAPM) with the Sharia Compliance Asset Pricing Model (SCAPM) in constructing an optimal stock portfolio based on the sharia stock index on the Indonesia Stock Exchange, specifically the Jakarta Islamic Index (JII), during the 2019–2023 period. The primary aim is to evaluate whether the SCAPM, which incorporates mudharabah profit-sharing returns in place of the risk-free rate, offers more relevant insights for Muslim investors compared to the CAPM. Utilizing a quantitative approach and a two-step regression method, the research develops an optimal portfolio by calculating stock betas and analyzing the relationship between systematic risk and expected returns. The findings reveal that neither the CAPM nor the SCAPM models are valid for predicting risk and expected returns for the JII's optimal stock portfolio. This study is intended to guide sharia-compliant investors in making informed decisions and assist investment managers in designing strategies aligned with Islamic financial principles.